Synthesis and Characterization of Some New Chalcones and Their Ti(III) and V(III) Complexes - Kumar Gangwar, Anuj; Rani Chaudhary, Ritu; Garg, Poonam (Asian Journal of Chemistry, 2010)
Some new chalcones have been prepared by the Claisen-Schmidt condensation using subtituted acetophenones and different aromatic aldehydes. Titanium(III) and vanadium(III) complexes of these synthesized chalcones have been prepared and characterized by elemental analysis, molar conductance, magnetic properties, electronic and IR spectral data. Octahedral geometry has been proposed for these metal chelates. Chalcones have been screened for their antimicrobial activities.